Evaluation of crop residue based complete rations through in vitro digestibility (Journal of Advanced Veterinary and Animal Research, 2014)
The present investigation was carried out to evaluate three potential complete rations made from locally available ingredients through in vitro digestibility (DM, CP, NDF and ADF) and in vitro total volatile fatty acids (TVFA) production. Three iso-nitrogenous complete rations comprising of maize stover (T1), red gram straw (T2) or black gram straw (T3) and concentrate in 60:40 ratio were prepared and the cost/kg diets were 5.2, 5.5 and 5.7 rupees/Kg diet, respectively. Three fistulated buffalo bulls (5 yrs, 350 ± 9.36 kg BW) used as donors of rumen inoculums were fed the same three complete rations (T1, T2 and T3) after proper adaptation. The three complete rations were iso-nitrogenous with CP content ranging from 12.62 to 12.82, while T3 contained higher EE (1.68 %) and TA (9.75 %) and higher NFE (34.38 %) in T1 than in other complete rations. However, variation was apparent in the fiber fractions of the three complete rations attributable to varying sources of the fibrous crop residues. Overall in vitro DM digestibility (IVDMD) and in vitro NDF digestibility (IVNDFD) % was higher (p